2012
DOI: 10.3389/fneur.2012.00004
|View full text |Cite
|
Sign up to set email alerts
|

Info Home About Editorial Board Archive Research Topics View Some Authors Review Guidelines Subscribe to Alerts Search Article Type Publication Date ...... Go Author Info Why Submit? Fees Article Types Author Guidelines Submission Checklist Contact Editorial Office Submit Manuscript Original Research ARTICLE This article is part of a Research Topic 0 Share Facebook Linkedin Like 0 Comment 0 Share 0 Fos expression in neurons of the rat vestibulo-autonomic pathway activated by sinusoidal galvanic vestibular

Abstract: The vestibular system sends projections to brainstem autonomic nuclei that modulate heart rate and blood pressure in response to changes in head and body position with regard to gravity. Consistent with this, binaural sinusoidally modulated galvanic vestibular stimulation (sGVS) in humans causes vasoconstriction in the legs, while low frequency (0.02–0.04 Hz) sGVS causes a rapid drop in heart rate and blood pressure in anesthetized rats. We have hypothesized that these responses occur through activation of ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 103 publications
3
45
1
Order By: Relevance
“…Such connections were demonstrated using cFos protein to identify vestibular neurons activated by sGVS (26). The sGVS-activated cells were concentrated in the caudal inferior and medial vestibular nuclei, otolith-recipient regions, and sent axonal projections to the rostral and caudal ventrolateral medullary areas (48).…”
Section: Discussionmentioning
confidence: 99%
“…Such connections were demonstrated using cFos protein to identify vestibular neurons activated by sGVS (26). The sGVS-activated cells were concentrated in the caudal inferior and medial vestibular nuclei, otolith-recipient regions, and sent axonal projections to the rostral and caudal ventrolateral medullary areas (48).…”
Section: Discussionmentioning
confidence: 99%
“…The immediate early gene protein c-Fos is useful for mapping functional activity of the brain [39,40]. Several studies have demonstrated that hypotension elicits c-Fos protein expression in several forebrain and brain stem nuclei that affect cardiovascular function [23,41].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical evidence shows the existence of a direct projection from vestibular nuclei to the RVLM region [40,48]. Functional convergence from the vestibular and baroreceptor afferents to the same nuclei in the RVLM further suggests that this is the central point of interaction between the vestibular system and the baroreflex [38].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies on animals indicate that the vestibular system projects to cardiovascular centres in the central nervous system through the vestibular sympathetic reflex and modulates blood pressure and heart rate in response to changes in the head and body position relative to gravity [9][10][11][12][13][14][15][16]. The anatomical connection of the vestibular sympathetic reflex pathway has been described in animals [17]. The activated cells in this pathway were concentrated in the caudal inferior and medial vestibular nuclei, otolithrecipient regions, and sent axonal projections to the rostral and caudal ventrolateral medullary areas [18].…”
Section: Introductionmentioning
confidence: 99%